Trends in valorization of highly-toxic lignocellulosic biomass derived-compounds via engineered microbes. (February 2022) - Jayakody, Lahiru N.; Chinmoy, Baroi; Turner, Timothy L.
Graphical abstract: Highlights: Lignocellulosic biomass-derived chemicals pose toxicity on microbes. Macromolecules protections are vital for tolerance engineering of microbes. Key metabolic routes are highlighted to biofunnel biomass-derived toxic chemicals. Robust synthetic microbes can valorize toxic chemicals to platform chemicals. Bioconversion of toxic chemicals enhances economic benefits to biorefineries. Abstract: Lignocellulosic biomass-derived fuels, chemicals, and materials are promising sustainable solutions to replace the current petroleum-based production. The direct microbial conversion of thermos-chemically pretreated lignocellulosic biomass is hampered by the presence of highly toxic chemical compounds. Also, thermo-catalytic upgrading of lignocellulosic biomass generates wastewater that contains heterogeneous toxic chemicals, a mixture of unutilized carbon. Metabolic engineering efforts have primarily focused on the conversion of carbohydrates in lignocellulose biomass; substantial opportunities exist to harness value from toxic lignocellulose-derived toxic compounds. This article presents the comprehensive metabolic routes and tolerance mechanisms to develop robust synthetic microbial cell factories to valorize the highly toxic compounds to advanced-platform chemicals. The obtained platform chemicals can be used to manufacture high-value biopolymers and biomaterials via a hybrid biochemical approach for replacing petroleum-based incumbents. The proposed strategy enables a sustainable bio-based materials economy by microbial biofunneling of lignocellulosic biomass-derived toxic molecules, an untapped biogenic carbon.